Sequential flue gas utilization for sustainable leaching and metal precipitation of spent lithium-ion battery cathode material: Process design and techno-economic analysis. (20th December 2022) - Kim, Jeongdong; Kim, Sangyoung; Lim, Jonghun; Moon, Il; Kim, Junghwan
Abstract: The growing use of lithium nickel manganese cobalt oxide (NCM) batteries has necessitated increased recovery of cathode materials for sustainable battery recycling given the limited metal source, and to mitigate the negative environmental impact of battery disposal. Acid leaching and the use of precipitants are essential for selective metal extraction in the recycling process. However, the excessive use of chemicals degrades the economic performance of the recycling process. In this study, we propose and simulate a novel lithium-ion battery (LIB) recycling system through sequential S O X, N O X, and C O 2 utilization of industrial flue gas in the following four processes: sulfuric acid and nitric acid regeneration from S O X, N O X, acid leaching of cathode materials, N a 2 C O 3 regeneration from sulfur and nitric-free flue gas, selective precipitation. In the sequential flue gas capture and utilization, the H 2 O 2 is used as a wet absorbent for both desulfurization and denitrification, and produces 3.3 M H 2 S O 4 and 7.18 M H N O 3 . NaOH is used for C O 2 utilization, and 2.32 M of N a 2 C O 3 is produced. We expected that the sequential flue gas utilization reduced the acids and precipitant consumption in the battery recycling process, which was more advantageous than the conventional recycling process by 2.70%. Highlights: First attempt at applying SOx, NOx, and CO2 capture and utilization (SCU, NCU, CCU) to the LIB recycling process. 3.3 M, 7.18 M, and 2.32 M of H2 SO4, HNO3, and Na2 CO3 are produced via the sequential flue gas utilization. Sequential flue gas utilization accomplishes 96.43% metal recovery efficiency. Proposed process was 2.70% more economical than the conventional process.